MODERN PARENTING CHALLENGES: PARENTS-CHILD COMMUNICATION BARRIERS AND SOLUTIONS IN THE DIGITAL ERA - Indah, Anggit Juliani; Nurhayati, Sri; Taufikin, Taufikin (JURNAL DIMENSI, 2025)
Parent-child communication is a cornerstone of family relationships and child development, fostering emotional bonds, trust, and social skills. However, modern family life introduces challenges, including emotional mismatches, time constraints, and the pervasive influence of technology. This study explores the barriers, strategies, and influences shaping parent-child communication within Kelurahan Linggajaya, Kecamatan Mangkubumi, Kota Tasikmalaya. The research focuses on parents with children aged 7-12 years, a critical developmental period marked by increasing autonomy and exposure to external influences. A descriptive qualitative approach was employed, with data collected through observation, semi-structured interviews, and document studies involving 20 parents. Thematic analysis revealed significant barriers, including emotional mismatches that lead to misunderstandings, time constraints that limit meaningful interactions, and technological distractions that reduce engagement. Despite these challenges, parents demonstrated resilience through strategies such as emotional awareness, active listening, and leveraging structured routines like mealtimes for communication. The study also highlights the dual role of technology, which facilitates remote connectivity but often disrupts face-to-face interactions, requiring parents to strike a delicate balance. These findings underscore the importance of adaptive communication strategies and the need for practical parenting resources to address the complexities of modern family life. The study contributes to the literature by offering insights into the intersection of emotional, technological, and developmental factors in a specific cultural context. Future research should explore children’s perspectives and long-term impacts on family cohesion and child development.